2016
DOI: 10.3748/wjg.v22.i15.3978
|View full text |Cite
|
Sign up to set email alerts
|

Mir-30d increases intracellular survival ofHelicobacter pylorithrough inhibition of autophagy pathway

Abstract: Mir-30d increases intracellular survival of H. pylori in gastric epithelial cells through inhibition of multiple core proteins in the autophagy pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…BCL2-interacting coiled-coil protein (BECN1) and autophagy-related protein 12 (ATG12) are two important proteins that guide other autophagy proteins to the pre-autophagosomal membrane and subsequently facilitating phagophore elongation and autophagosomes maturation 17 . Two groups have reported that H. pylori infection increases miR-30b/d and that compromised autophagy by miR-30b/d promotes bacterial replication by targeting BECN1 and ATG12 17 , 122 . DNA damage-regulated autophagy modulator 2 (DRAM2) is shown to interact with BECN1 as a coordinator of autophagy activation.…”
Section: Significance Of Altered Mirnas In Bacterial Infectionmentioning
confidence: 99%
“…BCL2-interacting coiled-coil protein (BECN1) and autophagy-related protein 12 (ATG12) are two important proteins that guide other autophagy proteins to the pre-autophagosomal membrane and subsequently facilitating phagophore elongation and autophagosomes maturation 17 . Two groups have reported that H. pylori infection increases miR-30b/d and that compromised autophagy by miR-30b/d promotes bacterial replication by targeting BECN1 and ATG12 17 , 122 . DNA damage-regulated autophagy modulator 2 (DRAM2) is shown to interact with BECN1 as a coordinator of autophagy activation.…”
Section: Significance Of Altered Mirnas In Bacterial Infectionmentioning
confidence: 99%
“…Compromised autophagy promotes persistent infection of H. pylori (71). Additionally, ATG2B, ATG5, ATG12, BECN1 and BCL2 interacting protein 3 like are targets of miR-30d, leading to the repression of autophagy (72). miR-30d further promotes the intracellular survival of H. pylori during chronic infection (72).…”
Section: Chronic Infection Of H Pylori Can Inhibit Autophagymentioning
confidence: 99%
“…Additionally, ATG2B, ATG5, ATG12, BECN1 and BCL2 interacting protein 3 like are targets of miR-30d, leading to the repression of autophagy (72). miR-30d further promotes the intracellular survival of H. pylori during chronic infection (72). Furthermore, H. pylori infection induces methylation silencing of microtubule associated protein 1 light chain 3α variant 1, which may impair autophagy and facilitate gastric carcinogenesis (73).…”
Section: Chronic Infection Of H Pylori Can Inhibit Autophagymentioning
confidence: 99%
“…As a result, a total of 17 candidate target genes (including ATG12, ATg2B, ATg5, BCL9, BECN1, BNiP3L, CASP3, EZH2, gNAi2, gPR78, KPNB1, NoTCH1, RUNX2, SMAD1, SNAi1, SoCS1 and TP53) for which the interaction between miR-30d was validated experimentally by reporter assay, western blotting and qPCR, were collected from miRTarBase for miR-30d. Among these genes, a previous study of Esposito et al (10) found that miR-30d directly targeted the 3'-UTR of EZH2 in anaplastic thyroid carcinoma. Growing evidence also showed that EZH2 overexpression was associated with tumor aggressiveness and poor prognosis in patients with ESCC (16-18).…”
Section: Mir-30d Reduces Ezh2 Expression By Targeting the 3'-utrmentioning
confidence: 99%
“…Abnormal expression of miRNAs has been observed in multiple types of human cancers, implying that miRNAs may function as either oncogenes or tumor suppressors by the sequence-specific regulation of the corresponding target gene expression (9). miR-30d, a member of the miR-30 family, is localized in human chromosome 8q24.22 (10). Accumulating evidence has revealed that the aberrant expression of miR-30d contributes to cancer development and progression.…”
Section: Introductionmentioning
confidence: 99%